Pengaruh Latihan Drill Terhadap Kemampuan Smash Bola Voli di SMA Negeri 1 Dampal Selatan - Murtono, Tri; Bulu Baan, Addriana Bulu Baan; Hendriana Sri Rejeki; Nyoman Sukrawan; Satriani; Bogy Restu Ilahi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Objective This study aims to determine the effect of drill training on volleyball smash skills in extracurricular students of Senior High School 1 Damsel. Smash is a primary attack technique that requires coordination, strength, and precision, but many students still have difficulty in performing it optimally. The research method uses a quantitative approach with a one-group pretest–posttest design. The sample consisted of 12 volleyball extracurricular students selected by purposive sampling. Data were collected through smash skill tests before and after treatment. Drill training was conducted for six weeks (16 meetings). Data analysis used a normality test and a paired sample t-test with a significance level of 0.05. Results The average pretest score showed a score of 33, while the posttest increased to 71 or an increase of 86.84%. The t-test results showed a significance of 0.00 <0.05 with a calculated t of 11.938> t table 2.201, so there is a significant effect of drill training on volleyball smash skills. Drill training has been proven to be effective in improving smash skills through systematic repetition of movements. This method is recommended for use in volleyball learning and extracurricular activities to optimize students' basic techniques.